2008
DOI: 10.1177/1359105308095058
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections

Abstract: The impact of having genital herpes and genital human papilloma virus (HPV) on individuals and their relationships was investigated. A qualitative research methodology explored the lived experiences of 30 adults with genital herpes (15 men, 15 women), and 30 adults with HPV (15 men, 15 women). This study addressed individuals' feelings about the impact of stigma associated with having an STI, the impact of having an STI on sexuality and on intimate relationships, and feelings surrounding the process of disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Whether BV is sexually transmitted remains unclear and somewhat controversial. While it is commonly acknowledged that considerable psychosocial sequelae and social stigma are associated with STI diagnoses [22][24], [29], [38] there have been very limited attempts to investigate whether women with vaginal conditions such as BV also experience similar feelings of shame, stigma and psychosocial sequelae. Given that, symptoms of vaginal malodour are commonly associated with unattractiveness, poor hygiene and/or sexual promiscuity, symptoms may be perceptible by others, BV is recurrent in nature, and there is considerable confusion on the part of both clinicians and patients as to whether BV is sexually transmitted, it is not surprising that women are experiencing poor self-esteem, sexual withdrawal, self-isolation and feelings of self-blame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether BV is sexually transmitted remains unclear and somewhat controversial. While it is commonly acknowledged that considerable psychosocial sequelae and social stigma are associated with STI diagnoses [22][24], [29], [38] there have been very limited attempts to investigate whether women with vaginal conditions such as BV also experience similar feelings of shame, stigma and psychosocial sequelae. Given that, symptoms of vaginal malodour are commonly associated with unattractiveness, poor hygiene and/or sexual promiscuity, symptoms may be perceptible by others, BV is recurrent in nature, and there is considerable confusion on the part of both clinicians and patients as to whether BV is sexually transmitted, it is not surprising that women are experiencing poor self-esteem, sexual withdrawal, self-isolation and feelings of self-blame.…”
Section: Discussionmentioning
confidence: 99%
“…A number of qualitative and mixed methods studies [22][24] have found that individuals with genital herpes or HPV commonly experience significant anxiety, self-blame and embarrassment around their diagnosis, and fear disclosing their status to others. Individuals often report feeling stigmatised, experiencing lowered self-esteem and concern around future sexual interaction and relationships [22][24].…”
Section: Introductionmentioning
confidence: 99%
“…deepening their relationships), these findings identify that in the earlier stages in the process, disclosure is experienced as aversive, difficult and intense. This property of HIV disclosure shares similarities to disclosing other stigmatized health conditions such as hepatitis C (Dunne & Quayle, 2002), genital herpes and the human papilloma virus (HPV) (Newton & McCabe, 2008). It has previously been stated that the transformation of HIV from a terminal to a chronic illness 'may mean that…disclosure has become easier' (Denis, 2014, p. 283), and so could be incorporated with disclosure research on the conditions named above.…”
Section: Discussionmentioning
confidence: 99%
“…Given that feelings of promiscuity and shame may accompany a herpes diagnosis (Bickford, Barton, & Mandalia, 2007), individuals may feel responsible for contracting it, which may lead to increased sensitivity to herpes-related stigma (Radecki Breitkopf, 2004). Although previous researchers have found evidence of herpes-related stigma (Newton & McCabe, 2008), its relationship to herpes-related psychological adjustment is unknown. This is an important question to answer, given that perceived stigma has been found to have an inverse relationship to physical and mental health (Major & O’Brien, 2005).…”
mentioning
confidence: 97%